Study of impact properties of materials by instrumented impact testing - Zheng, Qi. (2009)
Impact toughness improvement arising from delaminations has been studied by some researchers. However, the previous investigations were limited in scope because the impact testing was non-instrumented and the specimens used contained weak interfaces made artificially either by soldering thin mild steel plates together or by laminating high-strength titanium alloys and maraging steels. In contrast, in the present project, instrumented impact testing was carried out and the study focused on the toughening effect of delaminations formed from inherent weak microstructural or inclusion bands in various types of engineering materials. Delaminations occurred along rolling bands during the instrumented impact tests at -77°C and -196°C on sub-sized Charpy specimens extracted from a mixing chamber made of austenitic stainless steel. The rolling band-induced delaminations drastically improved the impact toughness at low temperatures of-77°C and -196°C and caused the "abnormally" high values of impact energy at -77°C and -196°C than those at higher temperatures. Further experiments were carried out on a much more degraded austenitic plate without obvious rolling bands from the same mixing chamber. In the latter material, rolling band-induced delaminations did not occur even at -196°C and the impact energy values were found to be largely independent of test temperature, as normally expected of an austenitic stainless steel. To further investigate the toughening effect of delaminations, additional instrumented tests were carried out on standard Charpy specimens of a mild steel with the inclusion band located at a different distance d away from the notch root. It was found that the maximum impact energy values were obtained when d=\. 1-1.2 mm at 25°C and 0°C because of the inclusion band induced-delamination. Finally, a duplex stainless steel was studied to investigate the effect of the ferrite-austenite duplex microstructures on the impact toughness and to examine whether the duplex microstructures can induce delaminations. The results obtained show that delaminations occurred at -196°C from the ferrite-enriched bands; however, the values of impact energy obtained at -196°C were lower than those obtained at higher temperatures due to the embrittlement of ferrite at -196°C.